Polyphony and Genre Hybridism in Lapidario (2004) by Miguel-Anxo Murado - Veiga, Martín (Madrygal. Revista de Estudios Gallegos, 2015)
This article reflects on the epitaph as literary form by looking at the main textual and paratextual differences between Miguel-Anxo Murado’s Lapidario and its predecessor Lapidario dos heterodoxos. It also examines the book’s complex uses of polyphony and genre hybridism as postmodern strategies which problematize the reading of this text as merely a poetry collection.